Inclusive Religious Education in a Democratic State: Forming Tolerant Character in a Multicultural Society - Rahman, Hanifah Aulia; Suwendi; Moh Ali; Ade Hidayat (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This research explores the concept and implementation of inclusive religious education within the framework of a democratic and multicultural society in Indonesia. As a country with diverse religions, ethnicities, and cultures, Indonesia faces both opportunities and challenges in strengthening tolerance through education. Using a qualitative approach with a literature review and case analysis in selected schools, the study examines how inclusive practices are integrated into religious education. The findings reveal that inclusive religious education significantly contributes to fostering tolerant character among students, improving interfaith understanding, and strengthening social harmony. Nevertheless, the study identifies several obstacles, such as limited teacher training in multicultural competence, inadequate teaching resources, and the insufficient integration of democratic values in the curriculum. The paper emphasizes that inclusive religious education will only be effective if supported by a strong policy framework, curriculum reform, and comprehensive teacher preparation. Therefore, this research recommends improvements in curriculum development, teacher education, and government policy to ensure that students are nurtured in an environment that cultivates tolerance, respect, and democratic values in a multicultural context